TRANSFORMASI MODEL PENDIDIKAN MATHLA’UL ANWAR: INTEGRASI NILAI DAKWAH DAN MODERNISASI LEMBAGA PENDIDIKAN ISLAM - Rahmi Nur Azizah; Suparto Suparto (Halaqah: Journal of Multidisciplinary Islamic Studies, 2025)
This study aims to analyze the transformation of the educational system within the Islamic organization Mathla’ul Anwar (MA) and to examine how da’wah values are integrated into its educational practices. Employing a qualitative approach through library research, this study draws upon primary and secondary sources, including scholarly journals, organizational archives, and historical literature on Islamic education in Indonesia. The findings reveal that since its establishment in 1916 in Menes, Banten, MA has developed an integrative educational model that combines religious and general sciences as a manifestation of da’wah bil-ḥāl, preaching through social and institutional action. The transition from a traditional to a modern educational system is reflected in the implementation of an integrated curriculum, the adoption of a classical classroom structure, and the institutional strengthening up to the university level. Moreover, the values of sincerity, nationalism, and progress serve as the moral foundations for all educational activities within MA. In conclusion, MA’s educational model represents a form of transformative cultural da’wah that harmonizes Islamic values, modern rationality, and national spirit. Through education, MA has positioned itself as a strategic agent of social reform and the development of a progressive Islamic civilization in Indonesia.